The Effect Of Multinationality And Transfer Pricing On Tax Avoidance Through Profitability - Barus, Berlin; Siregar, Zulkheiri Surya Putra; Silalahi, Dumariani; Silalahi, Harlen; Sihite, Jelita IP (Institut Bisnis dan Informatika Kesatuan, 2024)
Over the past decade, tax revenues from Indonesia’s palm oil industry have declined, despite increasing production volumes. This phenomenon raises concerns about potential tax avoidance practices. This study investigates the influence of multinationality and transfer pricing on tax avoidance, with profitability as a moderating variable. Using panel data from palm oil companies listed on the Indonesia Stock Exchange between 2013 and 2020, the study employs multiple regression analysis through the EViews application. A total of 112 firm-year observations were selected using purposive sampling. The findings reveal that multinationality has a positive and statistically significant effect on tax avoidance, while transfer pricing does not exhibit a significant effect. Moreover, profitability does not significantly moderate the relationship between either multinationality or transfer pricing and tax avoidance. The regression model explains 14.26% of the variance in tax avoidance (R² = 0.1426). These results highlight the need for strengthened tax oversight and regulatory measures in the palm oil sector, particularly regarding cross-border corporate structures. Keywords: multinationality, transfer pricing, tax avoidance, profitability, palm oil industry